COMPARATIVE STUDY OF USE OF E-CLASS APPLICATIONS AND ZOOM CLOUD MEETING ON LEARNING MOTIVATION AND STUDENT LEARNING OUTCOMES - Firmandani, Sandi; Sukrawan, Yusep (Journal of Mechanical Engineering Education (Jurnal Pendidikan Teknik Mesin), 2021)
Due to the pandemic, learning activities in schools must be carried out based on E-learning. The use of E-learning-based learning media is an alternative in online learning. One of them is the use of E-class and Zoom Cloud Meetings, which are expected to improve students’ motivation and students’ learning outcomes. This study aims to determine the comparison between E-class and Zoom Cloud Meetings on students’ learning motivation and students’ learning outcomes. This study uses an experimental method which uses quasi-experimental and non-equivalent control group design. This study took a sample using purposive sampling, with 2 experimental groups and 1 control group. This study also uses two applications, namely E-Class and Zoom Cloud Meetings, by comparing two variables: learning motivation and learning outcomes. Learning motivation and learning outcomes were analysed by descriptive statistical analysis and infertile statistical analysis. The findings of this study showed that there were significant differences in learning motivation and learning outcomes between the two experimental classes, both using Zoom Cloud Meetings application and E-class as indicated by the t-test. Meanwhile, the difference between learning motivation of participants in using E-class and Zoom Cloud Meetings proven by the characteristics of the categories of increasing learning motivation. Quiz features and main characteristics on E-class can increased students’ persistence as their motivation in doing tasks. Meanwhile the use of zoom cloud meetings application can increased learning motivation in terms of giving opinion in a discussion when online learning occurred, because it has a feature which teacher can see students directly. So that teachers can direct their students to be able to discuss with each other and can discuss with each other about the material being taught during the learning process.